The Analisis Technological Pedagogical Content Knowledge (TPACK) Pada Guru Ekonomi di Kota Cirebon - Rian Gunawan; Kusnendi; Budi Santoso (FKIP Unswagati, 2026)
This research is based on the result of the Teacher Competence Test in Indonesia, 2015 which is still below the standard value. The aim of this research is to test the seven TPACK variables, namely Technological Content (TK), Content Knowledge (CK), Pedagogical Knowledge (PK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK) Technological Pedagogical Content Knowledge (TPACK), tested on economic subject teachers at Cirebon Senior High Schools. This research used quantitative research with descriptive method. Instruments in this study is using questionnaires. From the results of 112 collected questionnaires calculated and analyzed using Structural Equation Modeling (SEM) approach. The result of the data analysis showed six positive influences, namely TK to TPK, TK to TCK, PK to TPK, TK to TCK, TPK to TPACK, and PCK to TPACK, while six other hypotheses proposed no significant effect. The results showed the factor that contributed the most on the TPACK model is Content Knowledge variable, with the role of indicator that provides the greatest contribution that is the teacher's knowledge of learning development strategy. Keywords: Economic Teacher, Economic Teachers' Competency, Technological Pedagogical Content Knowledge, TPACK